Modelling the influence of magnetospheric storm on the large-scale structure of the high-latitude ionosphere for winter solstice conditions - Gololobov Artem; Golikov Innokentiy; Popov Vasiliy (Solar-Terrestrial Physics)
Using numerical calculations with a model of the high-latitude ionosphere in Eulerian variables, we study the influence of magnetospheric convection on the large-scale structure of the ionosphere during a moderate geomagnetic storm for winter solstice conditions. The disturbed electric field of convection is shown to cause changes in the shapes and sizes of the main structural formations of the ionosphere. We have found out that the effect of a geomagnetic storm depends on the time of the beginning of the disturbance due to the mismatch between the geographic and geomagnetic poles (UT control). The effect is most pronounced in the case of a storm that begins at 16 UT, when the disturbed electric field of magnetospheric convection transfers plasma of the daytime ionosphere to the nightside. It is shown that during periods of disturbances along with the horizontal component of the electromagnetic drift its vertical component, which causes an increase in the height of the F2-layer maximum on the dayside and its decrease on the nightside, also has a significant effect.